Determination of sun protective factors (SPF) and antioxidant activity of ethanolic extract of rambutan rind (Nephelium lappaceum L.) - Ida Adhayanti; Nurisyah Nurisyah; Alfrida Monica Salasa; Arisanty Arisanty; Santi Sinala (School of Pharmacy Institut Teknologi Bandung, 2018)
Background, The fruit peels of rambutan (Nephelium lappaceum L)are organic garbage with many potential health benefits but have not been used optimally. Purposes This study aims to determine the sun protective factor (SPF) and antioxidant activity of ethanolic extract of rambutan rind. Methods The rambutan (Nephelium lappaceum L) rind was extracted by maceration method using ethanol as solvent. A simple, rapid and reliable in vitro method was used to assess the SPF values by measuring the absorbance of diluted extract between 290-320 nm at every 5 nm intervals using Ultraviolet Spectrophotometry. The SPF values were calculated based on the recorded absorbance using a simple mathematic equation developed by Mansur. The antioxidant activity of rambutan rind was determined by the 1,1-diphenyl-2-picryl-hydrazil (DPPH) assay whereas vitamin C as positive control. Results The SPF values of rambutan rind in concentration series of 50, 100, 150 and 200 ppm were 6,47±0,45 , 9,26±0,28, 13,01±0,33, and 16,17±0,63 respectively. The IC50 value of rambutan rind was 41,47 ± 3,89 µg/ml whereas the IC50 value of vitamin C was 24,87 ± 0,69 µg/ml. Conclusion Based on the result, the ethanolic extract of rambutan rind has potential as sunscreen and antioxidant.